Regional specialization, sustainable development and social economy: The case of Western Macedonia region - Staboulis, Miltiadis; Papagiannis, George (The Greek Review of Social Research, 2021)
This paper seeks to explore the role of regional specialization and the contribution of the social economy sector to the economically sustainable perspective of the region of Western Macedonia. Specifically, the regional specialization strategy of Western Macedonia is examined, in the context of the respective European strategy, in order to extract research results for the framework and its implementation. Research results on the economic environment, in the field of entrepreneurship and innovation, as well as on the sustainability and potential of the social economy sector in regional development are also presented.